2011
DOI: 10.1007/s00228-011-1046-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphism in the folate metabolic pathway with methotrexate pharmacokinetics and toxicity in childhood acute lymphoblastic leukaemia and malignant lymphoma

Abstract: A population pharmacokinetic model developed in this study implies only a limited influence of genetic factors on the systemic disposition of MTX. Clearance is moderately reduced in patients with the MTHFR 677TT genotype. Genetic polymorphisms in the folate metabolic pathway and SLC19A1 were associated with HD-MTX toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 46 publications
5
71
4
Order By: Relevance
“…In concordance with our previous studies, investigating HD-MTX pharmacokinetics3 and HDMTX-related toxicity in children with ALL4, we observed significantly higher AUC levels in carriers of at least one MTHFR 677T allele compared to patients with wild-type genotype. Similar to our findings, other studies also reported the influence of MTHFR 677T allele on higher MTX plasma levels 7,8.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In concordance with our previous studies, investigating HD-MTX pharmacokinetics3 and HDMTX-related toxicity in children with ALL4, we observed significantly higher AUC levels in carriers of at least one MTHFR 677T allele compared to patients with wild-type genotype. Similar to our findings, other studies also reported the influence of MTHFR 677T allele on higher MTX plasma levels 7,8.…”
Section: Discussionsupporting
confidence: 92%
“…Only patients with lymphoblastic T-cell NHL treated according to the BFM protocols3 who received HD-MTX during consolidation phase were included into the study group. Toxicity evaluation and HD-MTX pharmacokinetics data collection and analysis were described previously 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of MTHFR polymorphisms in mediating this risk again show mixed results, being confirmed by multiple high level studies [26,[67][68][69], yet having no association found in other studies [97]. Multiple SNPs in SLCO1B1, an MTX transporter gene; efflux transporter genes ABCB1, ABCC4; as well as genes otherwise involved in folate metabolism such as GSTM1 and GSTT1 have been variably linked with MTX plasma levels, hepatotoxicity, and the occurrence of mucositis [30, 46, 56-61, 98, 99].…”
Section: Gastrointestinal Toxicitymentioning
confidence: 89%
“…The present case developed toxicity despite the rescue, the probable factors to be considered are high dosage with respect to her body weight, not recognising the minor side effects initially and not advocating the double dose of leucovorin inspite of the advice and may be due to hypersensitivity to methotrexate because of MTHFR 2 mutations 11. The other reasons for methotrexate toxicity reported in the literature include genetic polymorphism in the folate metabolic pathway delaying the clearance of methotrexate,12 delay in renal excretion due to consumption of cola beverages,13 the state of hydration, concomitant drugs taken such as trimethoprim and sulphamethoxazole, and proton pump inhibitor like dilantin 14. Methotrexate clearance was moderately reduced in patients with the MTHFR 677TT.…”
Section: Discussionmentioning
confidence: 99%